Investigating the Governance of Students’ Soft Skills Development - Nurlaila Nurlaila; Nurul Fadhillah (ELITE JOURNAL, 2022)
Students at the university level are required to have some capacity and quality to be useful in their life, and it is related to soft skills. Developing quality in Indonesia requires more effort and new ways or programs for teachers and lecturers. This study aimed at investigating the governance of students’ soft skills development in IAIN Lhokseumawe. The research method applied in this research was descriptive qualitative. The subject of this research were four English lecturers and 80 students from four Faculties of IAIN Lhokseumawe. The data collection technique used in this research was Focus Group Discussion and observation. The data were analyzed qualitatively using three stages: data condensation, data display and conclusion drawing. The result of the governance of students’ soft skills development was shown in three steps; planning, implementing and evaluating. It was shown that the lecturers had included soft skills in their lesson plans; the semester lesson plans had been implemented adequately included in the evaluation; the assessment done by the lecturers included students’ soft skills, and the lecturer has set the types of evaluation in measuring or assessing the student soft skills. Keywords: Soft skills, research and development, students and graduates’ quality